Implementasi Pelaksanaan Program Kampus Mengajar Angkatan 8: Upaya Meningkatkan Numerasi, Adaptasi Teknologi, dan Karakter Siswa di SD Inpres Parangbanoa - Yumi Yulfira; Siti Walida Mustamin (CV. ITTC INDONESIA, 2025)
The Kampus Mengajar (Teaching Campus) Batch 8 Program is a strategic initiative to support the improvement of education quality in elementary schools, including at SD Inpres Parangbanoa. This article discusses the program's implementation, which aims to enhance students' literacy and numeracy skills, technology adaptation, climate change mitigation, and character development. However, this article specifically focuses on numeracy, technology adaptation, climate change mitigation, and character development. The method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The implementation results revealed various innovative activities, such as interactive numeracy tutoring, the introduction of technology-based learning media, raising environmental awareness through climate change mitigation programs, and strengthening character values through thematic activities. The main challenges faced were limited facilities and human resources, which were overcome through collaboration between teaching students, teachers, and school staff. This program has a positive impact on improving learning quality and building an inclusive and sustainable educational environment. It is recommended to enhance infrastructure support, develop teacher competencies, and expand the program's scope to benefit more schools.